Analytical Description of NMR Relaxation Highlights Correlated Dynamics in Intrinsically Disordered Proteins. Issue 45 (14th September 2017) - Salvi, Nicola; Abyzov, Anton; Blackledge, Martin
Abstract: The dynamic fluctuations of intrinsically disordered proteins (IDPs) define their function. Although experimental nuclear magnetic resonance (NMR) relaxation reveals the motional complexity of these highly flexible proteins, the absence of physical models describing IDP dynamics hinders their mechanistic interpretation. Combining molecular dynamics simulation and NMR, we introduce a framework in which distinct motions are attributed to local libration, backbone dihedral angle dynamics and longer‐range tumbling of one or more peptide planes. This model provides unique insight into segmental organization of dynamics in IDPs and allows us to investigate the presence and extent of the correlated motions that are essential for function. Abstract : Conformational dynamics of intrinsically disordered proteins (IDPs) define their biological function but remain poorly understood. By combining MD simulation and NMR, distinct contributions to this motion are identified, including backbone dihedral jumps and longer‐range segmental dynamics.